Faktor Yang Mempengaruhi Perilaku Pencegahan Covid-19 Di Pasar Rakyat - Mery Mery; Rara Marisdayana; Renny Listiawaty (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2023)
COVID-19 is still a pandemic throughout the country. The spread of COVID-19 is influenced by community activities, namely one market that has a high potential for the space of COVID-19, which must be a concern when health practices are implemented. The purpose of this study is to find out what factors influence COVID-19 prevention behavior. This research is quantitative research with a cross-sectional research design. The population in this study were all traders in the Pasir Putih People's Market, South Jambi District, Jambi City, totaling 132 people, and sampling was done using purposive sampling. In this study, the analysis was carried out univariately and bivariate by using the Chi-Square test, and the research instrument was a questionnaire. The results showed that there was a relationship between knowledge (p = 0.006), attitude (p = 0.000), facilities and infrastructure (p = 0.002), and the behavior of COVID-19 prevention at the Pasir Putih People's Market, South Jambi District, Jambi City in 2022, and there was no relationship between social support (p = 0.097) and COVID-19 prevention behavior. This study found that knowledge, attitudes, facilities, and infrastructure are closely related to the behavior of COVID-19 prevention at the Pasir Putih People's Market, South Jambi District, Jambi City.